Shaping Leadership Potential in Medical Students - Пономарьов, Володимир Іванович; Риженко, Марина Володимирівна; Ємець, Костянтин Миколайович (Проблеми сучасної освіти, 2018)
Nowadays, psychological and pedagogical sciences are eager to boost students’ interest in studies at higher educational institutions because it is a major factor affecting the development of student’s inner potential. The majority of works in this field deal with studies of the student’s personal potential, while the problem of the leadership potential development in students (i.e. development of leadership qualities directly in the educational environment of a pedagogical university) is understudied, particularly in students of pedagogical schools. The theoretical and methodological grounds for the research are the analysis of psychological and pedagogical understanding of leadership as a phenomenon of development of leadership skills in students. The article contains the results of the theoretical analysis of the leadership potential of a student’s personality development in the educational environment of a higher educational institution, defines the structure of a student’s leadership potential, and explores the content of the process of the leadership potential development in the educational environment of a pedagogical higher educational institution.